2007
DOI: 10.1097/fjc.0b013e3180408d8d
|View full text |Cite
|
Sign up to set email alerts
|

2-APB Induces Instability in Rat Left Atrial Mechanical Activity

Abstract: Atrial contractile abnormalities are common clinical disorders but few pharmacological models can reliably produce such abnormalities in isolated atrial muscle. Since sarcoplasmic reticulum (SR) calcium leak may underlie these contractile irregularities, we investigated whether 2-aminoethoxydiphenyl borate (2-APB), a calcium leak-inducer, affects mechanical function in isolated, superfused rat left atria. Exposing left atria paced at 3 Hz to >10 microM 2-APB produced sporadic mechanical events that occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…On the other hand, 2-APB has been reported to induce Ca 2+ store release [11,20]. Previous studies evidenced that 2-APB induced sporadic spontaneous mechanical activity in rat left atria [13]. In the present study, we found that 2-APB induced ectopic activity in rat atria and 2-APB-induced ectopic activity was inhibited by Na [24,29,30].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, 2-APB has been reported to induce Ca 2+ store release [11,20]. Previous studies evidenced that 2-APB induced sporadic spontaneous mechanical activity in rat left atria [13]. In the present study, we found that 2-APB induced ectopic activity in rat atria and 2-APB-induced ectopic activity was inhibited by Na [24,29,30].…”
Section: Discussionsupporting
confidence: 69%
“…Base on this understanding and the present results, the schematic illustration of 2-APBinduced atria ectopic activity was described as following ( Previous studies explored the mechanism of 2-APBinduced mechanical activity in isolated rat left atria. Wolkowicz et al reported that 2-APB-induced mechanical activity depended on the concentration of superfusate sodium, chloride, and potassium, and was sensitive to anion transport inhibitor, hyperpolarization-activated current (If) inhibitors [13,14]. These results indicated that the mechanism of 2-APB-induced mechanical activity in atria was complicated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found that 2APB provokes a novel type of arrhythmic activity [103][104][105][106] which appears to satisfy the demands of the focal source hypothesis of Engelmann and Scherf. In particular,…”
Section: Is Voltage-independent Calcium Signaling a Focal Source Of Asupporting
confidence: 57%
“…29,30 This discrepancy can be explained by the different dosages of 2-APB used in these studies as 2-APB suppresses IP 3 R-linked calcium signaling at low concentrations, while at higher concentrations it induces leakage from cell calcium stores. 29,30 A potential limitation is that it is still unknown whether changes of cytosolic Ca 2þ interfere with measurements of cytosolic Mg 2þ in HL-1 cells. But it is reported that cytoplasmic free Ca 2þ does not contribute significantly to Mg 2þ -Fura-2 intensity unless the concentration exceeds 1 mmol/L.…”
Section: Discussionmentioning
confidence: 94%